The changes of intracellular calcium concentration and distribution in the hard end pear (Pyrus pyrifolia cv. 'Whangkeumbae') fruit. (May 2018) - Wang, Yuling; Zhang, Xinfu; Wang, Yongzhang; Yang, Shaolan; Qu, Haiyong
Graphical abstract: A model for the role of calcium deficiency in the pear ( Pyrus pyrifolia cv. 'Whangkeumbae') fruit hard end disorder occurring. The low Ca 2+ influx leads to less Ca 2+ into the pear fruit, which results in an intracellular imbalance of Ca 2+, and consequently the Ca deficiency triggers the lignin accumulation in the pear fruit, which triggers the development of hard end disorder. The Ca treatment increased the Ca content via a mechanism which is most likely related to its inhibition of lignin synthesis, and thereby inhibited the hard end fruit. Ca with yellow shading represents the Ca which the fruit absorb, Ca with blue shading represents the 2% CaCl2 solution. Red arrow represents positive regulation, blue arrow represents negative regulation. Highlights: This study is the first report about the mechanisms that are involved in the hard end disorder development. We found the Ca deficiency triggers the lignin accumulation in the pear fruit, which triggers the development of hard end disorder. CaCl2 treatment increased the Ca content via a mechanism which is most likely related to its inhibition of lignin synthesis, and thereby inhibited the hard end development. Abstract: Hard end is a physiological disorder of pear fruit that is frequently observed in the 'Whangkeumbae' ( Pyrus pyrifolia ) variety, however, the mechanisms that are involved in its development are poorly understood. In this study, we explored the causes of hard end disorder in pear fruit in relation to calcium deficiency. During fruit development, the ratio of Ca/N, Ca/K, Ca/Mg and the content of B were significantly lower in the hard end fruit as compared to normal fruit. However, no calcium deficiency was detected in the soil and leaves of the orchard where the hard end fruit were located. Additionally, the Ca 2+ influx in the calyx of hard end fruit was lower than that of normal fruit at 90 d after anthesis. The free Ca 2+ and storage Ca 2+ in the flesh cells of hard end fruit were less than that of normal fruit during fruit development, while an opposite tendency was observed at 120 d after anthesis (harvest day). In hard end fruit, the Ca 2+ transport-related gene, PpCNGC1 (Cyclic nucleotide-gated ion channel 1), was up-regulated; whereas the Ca 2+ sensor-related genes of PpCIPKs, PpCDPK28 and PpCML41 were all down-regulated. Spraying with a 2% calcium chloride (CaCl2 ) solution inhibited the incidence rate of hard end disorder and decreased fruit firmness and lignin content during storage. Additionally, the ratio of Ca/N, Ca/K, Ca/Mg and the content of B all increased on harvest day. Our study suggests that low Ca 2+ influx leads to less Ca 2+ into the pear fruit, which results in an intracellular imbalance of Ca 2+ and consequently triggers the development of hard end disorder.